Implementation of an NGS‐based sequencing and gene fusion panel for clinical screening of patients with suspected hematologic malignancies. (30th July 2019) - Levy, Michael A.; Santos, Stephanie; Kerkhof, Jennifer; Stuart, Alan; Aref‐Eshghi, Erfan; Guo, Fen; Hedley, Ben; Wong, Henry; Rauh, Michael; Feilotter, Harriet; Berardi, Philip; Semenuk, Laura; et al.
Abstract: Objectives: The diagnosis of hematologic malignancies integrates multiple diagnostic and clinical disciplines. Historically, targeted (single‐analyte) genetic testing has been used as reflex to initial prescreening by other diagnostic modalities including flow cytometry, anatomic pathology, and clinical cytogenetics. Given the wide range of mutations associated with hematologic malignancies a DNA/RNA‐based NGS panel can provide a more effective and economical approach to comprehensive testing of patients as an initial, tier‐1 screen. Methods: Using a cohort of 380 patients, we performed clinical validation of a gene panel designed to assess 40 genes (DNA), and 29 fusion driver genes with over 600 gene fusion partners (RNA), including sample exchange data across three clinical laboratories, and correlation with cytogenetic testing results. Results: The clinical validation of this technology demonstrated that its accuracy, sensitivity, and specificity are comparable to the majority of targeted single‐gene approaches, while assessment of the initial patient cohort data demonstrated a high diagnostic yield of 50.5%. Conclusions: Implementation of a tier‐1 NGS‐based protocol for gene panel screening provides a comprehensive alternative to targeted molecular testing in patients with suspected hematologic malignancies, with increased diagnostic yield, scalability, reproducibility, and cost effectiveness, making it ideally suited for implementation in clinical laboratories.